Effectiveness of Employee Performance Output Through the Implementation of The Performance Architecture Method at Palu City Hospital - Pratiwi, Nanda; Suarayasa, Ketut; Rahman, Abd (Rifa'Institute, 2025)
Introduction: Performance gaps remain in Indonesian health services, as seen between Undata Regional General Hospital and Anutapura Regional General Hospital. Although Undata Regional General Hospital applies a Performance Architecture system, its effectiveness is uncertain. This study compares employee performance between the two hospitals. Objective: This study aims to compare employee performance between the two hospitals to evaluate whether the Performance Architecture system contributes to measurable improvements. Method: A quantitative comparative study was conducted with 95 purposively selected employees. Independent sample t-tests assessed differences in performance variables between both hospitals. Result and Discussion: Significant differences were found in Work Productivity (p = 0.018) and Service Quality (p = 0.024), with higher scores at Anutapura Regional General Hospital, indicating that Performance Architecture has not yet improved outcomes at Undata Regional General Hospital. No significant differences were observed in Procedural Compliance, Collaborative Ability, or Initiative and Adaptability. Conclusion: Performance Architecture at Undata Regional General Hospital has not produced optimal results. Stronger implementation and organizational support are needed to enhance performance